Pranatamangsa agricultural accounting: Regulated fees as guarantees for farmers' income at cost-revenue exchange rates - Whedy Prasetyo; Yosefa Sayekti (Journal of Accounting and Investment, 2023)
Research aims: Pranatamangsa calendar serves as a local wisdom genius to determine agricultural accounting for farmers' income.Design/Methodology/Approach: A qualitative method with an eco-phenomenology approach was used to reveal season markers.Research findings: Agricultural accounting presence through yield calculation embodies Farmer Exchange Value as income, with the use of pranatamangsa to increase harvest. This calculation is based on the calculation of planting costs to make the cost components that can be calculated, namely input and output costs to be managed by farmers as a formulation of farmer income, which is about costs paid (Ib) with prices received (It) added to the season factor as cost-revenue exchange rate determinants.Theoretical contribution/Originality: Agricultural accounting becomes an aspect based on concern for setting seasons. Disclosure or reporting of seasons through pranatamangsa agricultural accounting reports is the cost-revenue exchange rate as farmer income.Practitioner/Policy implication: The formulation that becomes farming income is multiplying the paddy production amount by the selling price of paddy per ton. The formulation considers the season factor as a determinant of harvest production. This formulation produces integrated, relevant agricultural accounting information based on season markers.Research limitation/Implication: It is necessary to further develop the results of public awareness as a form of the presence of agricultural accounting. Furthermore, research methods can use a positivist approach with harvest variable determinants. In addition, descriptive, causal, and qualitative studies can use ethnomethodology or phenomenology based on participant observation as a complete source.